The scarring effects of initial labor market conditions on South Korean nurses - Saade, Ahmed J.; Alexiou, Constantinos; Belghitar, Yacine (Seoul National University, 2024)
Using a longitudinal dataset spanning the period 2000-2020, and an identification strategy based on instrumental variables, we examine the existence of scarring in the context of the Korean nursing profession. We find that the prevailing unemployment rate at time of graduation has negative effects on nurses’ wages that remain highly significant up to 6 years after joining the labor market, while working hours are positively scarred for up to 10 years. We also estimate a series of happiness equations to understand nurses’ experiences after joining the labor market, and find that a higher unemployment rate at time of graduation is associated with feelings of worse financial conditions, less happy lives, and lower income satisfaction.
Keywords: Human capital; Persistence; Scarring; School-to-work transition; Unemployment